Dampak Dinamika Muka Air Tanah pada Besaran Dan Laju Emisi Carbon Di Lahan Rawa Gambut Tropika - L. Budi Triadi; Fengky F. Adji; Yudi Lasmana (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2018)
Drainage of peatlands will lower the water table, decompose the organics matter and increases the fire risk. Therefore knowledge of C emission rate is very important for drainage system planning, in order to preservepeat. Scientific methods that used in this study: calculation of thickness/ depth of the peat, peat volume, oxidized peat volume, C dry peat weight and CO2 equivalent. The rate of emission C is calculated on the basisof emission C and subsidence time. Furthermore, the emission rate C (Mton CO2/ yr) is calculated based on 4 (four) model/ scenario concepts, i.e: actual/ existing condition, plantation, canal blocking and canal blocking with reforestation. This activity was conducted in Sei Ahas, Kapuas, Central Kalimantan and Sungai Buluh, Tanjung Jabung Timur, Jambi. Based on research, it was found that land use change will greatly affect the change of ground water level of peat that contributes to increases the emission of C to the atmosphere.